Collocations with the word «voice» and their translation problems - A, Akbarov A. (Farabi Journal of Social Sciences, 2019)
Abstract. The choice of the word collocations in languages is more arbitrary than not. Why some languages say «at the station,» while others «on the station,» is yet to be understood. Again, while some languages use certain collocations with the words, the other languages do not recognize that usage. This leaves us with the blank space, or in best case, the circumlocution when translating the phrases from one language into another. In our study, we have examined the collocations of four different languages and their equivalents in the English language. Arabic, Bosnian, Portuguese, Italian, Spanish and English were compared in terms of the word «voice» and its collocations. Italian, Portuguese, Spanish being three languages of the same – Latinfamily, andthe Bosnian language and the Arabic language, which share a historical background were examined. The difficulties of translation due to the various reasons and (di)similarities were discussed.